2008 34th European Conference on Optical Communication 2008
DOI: 10.1109/ecoc.2008.4729296
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a full duplex PON featuring 2.5 Gbps sub carrier multiplexing downstream and 1.25 Gbps upstream with colourless ONU and simple optics

Abstract: We demonstrate a full-duplex DPSK SCM PON operating at 2.5Gbps/1.25Gbps bitrates, with RSOA ONU and simplified scheme. It achieves low sensitivity and is implemented with low-cost components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The transmission medium is shared among the ONUs in the upstream direction and a channel arbitration mechanism is adopted to avoid collisions from multiple ONU transmissions. The arbitration method of choice in the first generation commercial deployments has been time division multiple access (TDMA), [16], [17], but prototypical, symmetric bandwidth PONs based on wavelength division multiplexing (WDM) [18], sub-carrier multiplexing (SCM) [19], optical code division multiplexing (OCDMA) [20] and others have been extensively reported in the literature. PONs are also known as Fiber-To-The-Home/ Premises (FTTH/P) networks and are now formally part of the of the Ethernet protocol, (EPON), by IEEE [21].…”
Section: A Commercial Passive Optical Networkmentioning
confidence: 99%
“…The transmission medium is shared among the ONUs in the upstream direction and a channel arbitration mechanism is adopted to avoid collisions from multiple ONU transmissions. The arbitration method of choice in the first generation commercial deployments has been time division multiple access (TDMA), [16], [17], but prototypical, symmetric bandwidth PONs based on wavelength division multiplexing (WDM) [18], sub-carrier multiplexing (SCM) [19], optical code division multiplexing (OCDMA) [20] and others have been extensively reported in the literature. PONs are also known as Fiber-To-The-Home/ Premises (FTTH/P) networks and are now formally part of the of the Ethernet protocol, (EPON), by IEEE [21].…”
Section: A Commercial Passive Optical Networkmentioning
confidence: 99%
“…Several architectural, optical, electrical and signal processing techniques have been proposed to mitigate the impact of RB [16][17][18][19][20]. Interest has also been shown toward using radio frequency (RF) subcarrier multiplexing (SCM) as a simple and low cost means to reduce these effects [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous SCM implementations have generally been limited to asymmetric and/or subgigabit data rates by the RSOA's bandwidth and the use of guard bands to separate the uplink and downlink RF spectra and facilitate electrical filtering [22,23,25]. Recently, the authors demonstrated a novel overlapped-SCM (O-SCM) architecture that permits up to 2.5 Gb/s symmetric data rates by reducing the guard band and introducing an overlap between the received uplink and residual downlink spectra [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a single feeder PON, when the RSOA seed light has the same wavelength as that used for the downlink transmission, the system performance is severely degraded by Rayleigh backscattering [5]. Recently, subcarrier multiplexing (SCM) has been proposed to mitigate such degradation [5][6][7][8]. SCM may be used either for the uplink or the downlink, or for both transmissions as in [6].…”
Section: Introductionmentioning
confidence: 99%